The turbinal skeleton of Pentalagus furnessi (Leporidae, Lagomorpha) - Irina Ruf (Vertebrate Zoology, 2022)
The turbinal skeleton inside the nasal cavity supports the respiratory and olfactory epithelia of the mammalian nose and can provide systematic and morphofunctional information. For the first time, the turbinal skeleton of Pentalagus furnessi (Amami rabbit) from Japan is described based on µCT scans and virtual 3D reconstructions of two specimens. In general, the turbinal skeleton of Pentalagus furnessi resembles the pattern and characters observed in other Leporidae. The maxilloturbinal is highly dendritic, nasoturbinal and crista semicircularis are in close contact and form a common recess, the frontoturbinal recess houses two frontoturbinals and one interturbinal between them, the ethmoturbinal recess houses three ethmoturbinals and one interturbinal between ethmoturbinal I and II. Pentalagus furnessi is derived from the leporid grundplan in having a lamina semicircularis with almost straight posterior margin and ventral lamella and in showing a single-scrolled and relatively short interturbinal between frontoturbinal 1 and 2. These characters can be regarded as autapomorphic for the Amami rabbit. Furthermore, the two specimens have an additional small and short interturbinal between frontoturbinal 2 and ethmoturbinal I that shows some variation. This pattern supports previous observations of intraspecific variation of certain interturbinals in Oryctolagus cuniculus and some Sylvilagus and Lepus species. The comparison of the turbinal skeleton of Pentalagus furnessi and its possible sister taxon (e.g., Pronolagus, Poelagus or Caprolagus) reveals a puzzling pattern which is discussed.